INDEKS KEANEKARAGAMAN KOMUNITAS FITOPLANKTON SEBAGAI BIOINDIKATOR SAPROBITAS PERAIRAN DI SEKITAR PEMBANGKIT LISTRIK TENAGA UAP (PLTU) KABUPATEN NAGAN RAYA - Munandar Munandar; Neneng Marlian (JURNAL PERIKANAN TROPIS, 2017)
This research aims to know the structure of the phytoplankton community in waters of PLTU Nagan Raya and to know the index of saprobitas based on the quality of waters in physics and chemistry of water. Research methods are laboratories where data research results obtained from the measurement results directly (in situ). The analysis conducted in the laboratory include identification and measurement of physical and chemical parameters of the water. The parameters in the observed in this research is phytoplankton abundance, diversity index, uniformity coefficient, saprobik, domination, phytoplankton, and water quality index. The results of the research there were 21 types of Phytoplankton Composition, from the 5th Division Cyanophyta, Euglenophyta, namely Chryshophyta, Bacillariophyta and Chlorophyta. The average phytoplankton abundance ranged from 20-72 cells/l, with an abundance of phytoplankton dominated Chryshophyta i.e. 42,66-2,66%. Judging from the average index of diversity IE 0-2.23; the uniformity that is 0-0.73; the dominance of 0 – 0.72; with saprobitas coefficients of phytoplankton ranges from 0.25 – 1.18 and average water quality index range 6.2466 – 63.6272; The result indicates the quality of the waters to provide moderate to very bad.